Desarrollo de un videojuego para dispositivos móviles basado en un zoológico con hábitats capturados en 360° y gráficas en 2D - Espinosa Proaño, Ricardo Daniel (2019)
Ecuador is a country with unique natural ecosystems in the world, its fauna and flora make up a large part of the world's biodiversity. The Guayllabamba Zoos mission is to recover these ecosystems and eliminate the indiscriminate hunting of species, for this it offers conservation talks and offers volunteers to spread its message. Through the zoo, the foundation obtains funds for the maintenance of the zoo species which have been rescued and bred in captivity. This project aims to draw the attention of Ecuadorians to visit the zoo, reaffirm the environmental commitment and be aware of the work of the foundation. With TIC a striking and new experience is created, never before developed in Ecuador. The creation of habitats in 360 for mobile devices included in a flashy and intuitive video game is what Ecuador needs, not only to contribute to the zoo but to demonstrate that Ecuador can also create new interactions and arouse the interest of investment and research in this field. It is still unexplored and exploited in the country.